2010
DOI: 10.1111/j.1442-200x.2010.03164.x
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus in children: Causes, clinical features and short‐term outcome

Abstract: In our study, the risk factors for seizure recurrence were the presence of prior epilepsy, existence of neurological abnormalities and remote symptomatic causes. We argue that improving the compliance of patients and their families to take medicine appropriately and training them in how to cope with febrile illnesses may decrease the recurrence of seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
3
13
1
3
Order By: Relevance
“…Our results are in coherence with other studies from India and outside which have shown GTCS as the most common type of seizure. [ 15 20 25 26 ] Although the majority of patients with SE have GTCSs, some studies indicate that partial seizures also represent a major type of SE in children which is contradictory to our results. Besli et al .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are in coherence with other studies from India and outside which have shown GTCS as the most common type of seizure. [ 15 20 25 26 ] Although the majority of patients with SE have GTCSs, some studies indicate that partial seizures also represent a major type of SE in children which is contradictory to our results. Besli et al .…”
Section: Discussioncontrasting
confidence: 99%
“…[ 9 15 ] Studies outside India have also found male predominance for SE in children. [ 2 20 21 ] However, to the best of our knowledge, no definite causal relationship was found in literature for this male preponderance and warrants further investigation in future studies. However, there have been few studies which have found female preponderance for SE in children.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…7,25 As seizure duration lengthens, spontaneous resolution becomes more difficult, and this may particularly be true of febrile seizures. 7,13,26,27 Delays in treatment of FSE have been observed in previous studies. 10,16,26 A review of the Virginia Commonwealth University SE database, which includes all SE and both pediatrics and adults, found that less than half of SE patients received their first dose of an AED within 30 min of seizure onset.…”
Section: Discussionsupporting
confidence: 52%
“…5 The incidence is more common in male children 33(63%).Similar male preponderance is seen in a study done by Besli and Saltik. 6 The cause of convulsive status epilepticus varies across age groups. Shinnar et al in their study has shown that febrile status epilepticus and acute symptomatic etiologies are more common in children less than 2 years whereas remote symptomatic and idiopathic etiologies are common in older children.…”
Section: Discussionmentioning
confidence: 99%